Pengelolaan Kompetensi Sosial Guru Sekolah Dasar Negeri 2 Mojorebo Kecamatan Wirosari Kabupaten Grobogan - Junaiah, Junaiah, Prof. Dr. Sutama, M.Pd, Dr. Suyatmini, M.Si (2016)
This research activity aims to examine in depth descriptions of the management of social competence of teachers SD Negeri 2 Mojorebo Wirosari Grobogan on aspects be inclusive, to act objectively, and not discriminatory for consideration gender, religion, race, physical condition, family background and social status economy as well as on aspects of effective communication, empathic, and courteous to students, fellow teachers, staff, parents, and community. This type of research make use of a qualitative approach, descriptive qualitative design with phenomenology which describes views and opinions of informants based on circumstances or facts that exist in the environment around SD Negeri 2 Mojorebo. Sources of data obtained from the principal, teachers, students, observation, and documentation collection techniques triangulation or a combination of interview data, obsrvasi participatory, and documentation study. Analysis of the data used is interactive analysis consists of three components: data reduction, data presentation and conclusion. Based on the results of the analysis of the research objectives are: 1) Primary School Teachers Negeri 2 Mojorebo own social competence both in being inclusive, acting objectively, and not discriminatory, 2) Primary Teachers Negeri 2 Mojorebo own social competence both in communicating effectively, empathetic and polite with fellow educators, staff, parents, and the community, so that the learning outcomes achieved in State Elementary School 2 Mojorebo Subdistrict can be increased in line with expectations. Keywords: be inclusive, acting objectively, teacher competence, management.